Pendampingan Manasik Haji Di SDIT Al-Hikam Purwodadi - Siti Mastiyah; Kholis Aniyati (Jurnal Pengabdian Kepada Masyarakat, 2026)
The Hajj ritual practice is a form of Islamic religious education learning that aims to provide students with an understanding of the procedures for implementing the Hajj pilgrimage in both theory and practice. This community service initiative aims to describe the implementation of Hajj ritual mentoring at SDIT Al-Hikam Purwodadi. The results of the activity show that Hajj mentoring can improve students' understanding of the pillars and mandatory requirements of Hajj, instill values of discipline, togetherness, and responsibility, and foster a spirit of worship from an early age. The program was carried out through simulations of Hajj rituals such as ihram, tawaf, sa'i, wuquf, throwing pebbles (jamarat), and tahallul using learning media that mimic real conditions. This activity also received strong support from teachers and students' parents, making the learning process more effective and meaningful.